Variation in clearance and invasiveness of pharmacokinetic studies in children - Altamimi, Mohammed Ibrahim (2016)
Inter-individual variation in pharmacokinetic parameters of drugs can have profound effects on drug safety in children. Midazolam and morphine are among the most commonly used drugs in critically children. Theophylline has seen several cycles of enthusiasm and unpopularity over the years, although oral theophylline is now rarely used, IV aminophylline is still used regularly in severe asthma. These drugs are metabolised by hepatic enzymes (CYP3A4, CYP1A2 and glucuronidation) which have variable expression. Three systematic reviews were conducted in order to explore the inter-individual variation of clearance of these drugs in children.